Characteristics and function of the gut microbiota in patients with IgA nephropathy via metagenomic sequencing technology - Yang Deng; Zhiqiang Nong; Meiju Wei; Yuanshan Xu; Yuzhen Luo; Xiaohua Li; Ruobei Zhao; Zhenhua Yang; Ling Pan (Renal Failure)
Objective The aim of this study was to investigate the characteristics and related functional pathways of the gut microbiota in patients with IgA nephropathy (IgAN) through metagenomic sequencing technology.Methods We enrolled individuals with primary IgAN, including patients with normal and abnormal renal function. Additionally, we recruited healthy volunteers as the healthy control group. Stool samples were collected, and species and functional annotation were performed through fecal metagenome sequencing. We employed linear discriminant analysis effect size (LEfSe) analysis to identify significantly different bacterial microbiota and functional pathways. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was used to annotate microbiota functions, and redundancy analysis (RDA) was performed to analyze the factors affecting the composition and distribution of the gut microbiota.Results LEfSe analysis revealed differences in the gut microbiota between IgAN patients and healthy controls. The characteristic microorganisms in the IgAN group were classified as Escherichia coli, with a significantly greater abundance than that in the healthy control group (p < 0.05). The characteristic microorganisms in the IgAN group with abnormal renal function were identified as Enterococcaceae, Moraxella, Moraxella, and Acinetobacter. KEGG functional analysis demonstrated that the functional pathways of the microbiota that differed between IgAN patients and healthy controls were related primarily to bile acid metabolism.Conclusions The status of the gut microbiota is closely associated not only with the onset of IgAN but also with the renal function of IgAN patients. The characteristic gut microbiota may serve as a promising diagnostic biomarker and therapeutic target for IgAN.